Showing Their True Colors? How EU Flag Display Affects Perceptions of Party Elites' European Attachment. (December 2016) - Dumitrescu, Delia; Popa, Sebastian Adrian
Evidence suggests that incidental national flag exposure activates nationalistic feelings and that incidental exposure to the EU flag can affect citizen attachments to Europe. However, we know little about what inferences citizens make based on the EU flag when they see it displayed by parties in an electoral context. To test the expectation that this display affects citizens' evaluations of party elites' EU attachment, we conducted a large-scale experiment embedded in a Swedish survey in which respondents were exposed to communications from one of the two main Swedish parties, containing or not containing the image of the flag. We find that simple visual display does little to move perceptions. However, if citizens perceive that a particular party displayed the flag, then they are more likely to evaluate its party elites as more attached to Europe.